2006
DOI: 10.1038/nrd2055
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and development of clofarabine: a nucleoside analogue for treating cancer

Abstract: The treatment of acute leukaemias, which are the most common paediatric cancers, has improved considerably in recent decades, with complete response rates approaching approximately 90% in some cases. However, there remains a major need for treatments for patients who do not achieve or maintain complete remission, for whom the prognosis is very poor. In this article, we describe the challenges involved in the discovery and development of clofarabine, a second-generation nucleoside analogue that received acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
214
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(227 citation statements)
references
References 42 publications
4
214
0
6
Order By: Relevance
“…The dose and schedule-dependent cancer activity of clofarabine was demonstrated by testing different dosing schedules in an NCI H460 lung tumor 21 murine model with the greatest anti-tumor activity seen when the daily clofarabine dose was subdivided into three equal doses and administered at 4-hour intervals each day for 30 days [36,51].…”
Section: In Vivo Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dose and schedule-dependent cancer activity of clofarabine was demonstrated by testing different dosing schedules in an NCI H460 lung tumor 21 murine model with the greatest anti-tumor activity seen when the daily clofarabine dose was subdivided into three equal doses and administered at 4-hour intervals each day for 30 days [36,51].…”
Section: In Vivo Investigationsmentioning
confidence: 99%
“…When given to male and female patients with ALL or AML, clofarabine exhibits balanced clearance, with a renal clearance of 10.8 L/h/m 2 (28.8 L/h/m 2 total systemic clearance) with 57% of the dose being excreted unchanged in the urine [36]. The pharmacokinetics of clofarabine were further examined in 52 adults with solid tumors involved in a dose-escalation phase I study with doses up to 129 mg/m 2 administered once a week for 3 weeks every 28 days [66].…”
Section: Pharmacokinetic Data In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Clofarabine (2-chloro-2-fluoro-deoxy-9-D-arabinofuranosyladenine) is a second generation purine nucleoside analogue designed to maintain the favorable qualities of fludarabine without dose-limiting neurotoxicity. 15 In particular, single agent clofarabine is active in heavily pre-treated, relapsed and/or refractory patients with acute lymphoblastic leukemia and acute myeloid leukemia, [16][17][18] including older patients with high-risk features. 19,20 In addition, in vitro studies have shown synergistic activity between clofarabine and alkylating agents.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, deoxyadenosine-based analogues such as cladribine and fludarabine ( Figure 1) have both been shown to be active against various forms of leukemias and lymphomas (reviewed in [1]). Clofarabine, a second generation chemotherapeutic agent developed following the effectiveness of fludarabine, is active against several hematological malignancies, including acute and chronic leukemias (reviewed in [2]), myelodysplastic syndromes [3], and advanced pediatric acute leukemias [4].…”
Section: Introductionmentioning
confidence: 99%